Symbolic demonstrations in MuPAD-Combinat - Abbad, Houda; Laugerotte, Éric (INFOCOMP Journal of Computer Science, 2008)
This paper reports on a platform integrated to the open source package MuPAD-Combinat dedicated to the computation with rational expressions. Its main feature is the capacity of dealing with expressions whose scalars may belong to various algebraic structures. The paper describes some features of the platform as well as the data structures used in the implementation, details some algorithms and presents several illustrations of symbolic computations.